The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijms19113306
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Alzheimer’s Disease: Role of Insulin Signalling and Therapeutic Implications

Abstract: In the last two decades, numerous in vitro studies demonstrated that insulin receptors and theirs downstream pathways are widely distributed throughout the brain. This evidence has proven that; at variance with previous believes; insulin/insulin-like-growth-factor (IGF) signalling plays a crucial role in the regulation of different central nervous system (CNS) tasks. The most important of these functions include: synaptic formation; neuronal plasticity; learning; memory; neuronal stem cell activation; neurite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 121 publications
2
127
0
4
Order By: Relevance
“…Alzheimer's disease (AD), the most common cause of dementia [6], is characterized by the accumulation of amyloid β (Aβ) and hyper-phosphorylation of the Tau protein, with additional reduced acetylcholine levels and cerebral blood flow [2,7]. Furthermore, modifications in the blood-brain barrier (BBB), oxidative stress, mitochondrial impairment, neuroinflammation, and alterations in the insulin signaling have been observed in this condition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD), the most common cause of dementia [6], is characterized by the accumulation of amyloid β (Aβ) and hyper-phosphorylation of the Tau protein, with additional reduced acetylcholine levels and cerebral blood flow [2,7]. Furthermore, modifications in the blood-brain barrier (BBB), oxidative stress, mitochondrial impairment, neuroinflammation, and alterations in the insulin signaling have been observed in this condition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we investigated other causative factor such as inflammatory process, mitochondrial dysfunction, or oxidative stress that may have a more critical role in the synaptic and cognitive deficits in T2DM (Carvalho et al, ; Chornenkyy, Wang, Wei, & Nelson, ; Ling et al, ; Pintana et al, ; Tumminia, Vinciguerra, Parisi, & Frittitta, ; Verdile et al, ). In addition, others authors have shown that db/db mice have reductions in brain weight and spine density, which were worsened in APP/PS1xdb/db mice, indicating a role for Aβ in these deficits (Infante‐Garcia, Ramos‐Rodriguez, Galindo‐Gonzalez, & Garcia‐Alloza, ).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, affects other signal transduction pathways, including threonine-serine protein kinase, glycogen synthase kinase 3 beta (GSK3β) and the FoxO transcription factor family. For many of these paths, a key role in the proper functioning of the brain is assigned [55]. T2DM is a disease with a dynamically changing course, progressing from dominant insulin resistance, through compensatory hyperinsulinemia, to the exhaustion of the secretory capacity of pancreatic β cells.…”
Section: The Role Of Insulin Signaling In the Amyloid β Cascadementioning
confidence: 99%
“…The intraneuronal inclusion of the microtubule-associated protein tau serves as another established biomarker for AD. Tau protein, known to increase gradually with age from <300 pg/mL (21-50 years) to almost <500 (>71 years), demonstrates a significant exponential increase in AD sufferers from >450 to >600 pg/mL (in age rage [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70], hence proving to be a good prognostic biomarker [119]. AD exhibits the condition of tau protein being phosphorylated in almost 39 possible sites, with position 181 working as a definite biomarker in AD.…”
Section: Diagnostic and Potential Ad Biomarkers From Cerebrospinal Fluidmentioning
confidence: 99%